¡No pasarán!, Julio 1936. ¡Pasaremos!, Julio 1937 - Puyol (Sociedad General de Publicaciones, 1937)
Colour lithograph; yellow peasant and blue soldier marching with rifle Suggested translation: They shall not pass! July 1936. We shall pass! July 1937 PO-0118